Depressive symptoms and association with prevalent cardiovascular disease: A cross-sectional analysis in Port-au-Prince, Haiti - Daniella Myriam Pierre; Rehana Rasul; Reichling St. Sauveur; Kelly Celestin; Vanessa Rouzier; Erline Hilaire; Marie Marcelle Deschamps; Jean William Pape; Lily D. Yan; Anju Ogyu; Catherine Bennett; Margaret L. McNairy; et al. (PLOS Mental Health, 2026)
Cardiovascular disease (CVD) is the leading cause of mortality in low- and middle-income countries, and depression remains an underexplored CVD risk factor in Haiti. We assessed the association between depressive symptoms (DS) and prevalent CVD in urban Haiti and examined sex differences using a cross-sectional analysis of enrollment data from the Haiti Cardiovascular Disease Cohort (adults ≥18 years; March 2019–August 2021). DS were measured using the Patient Health Questionnaire-9 and categorized as none–mild (